Occupational Stress, Organizational Commitment, Career Commitment, Job Satisfaction and Withdrawal Cognition Among School Teachers - Cheng, Fun Keoh (2002)
Teachers form an important occupational group in the Malaysian government service. With the implementation of various educational changes and reforms in this country, teachers are experiencing higher expectations, greater responsibilities, more challenging roles, and also rising emotional and intellectual demands. Teachers are also facing more psychological and mental related problems, as well as emotional stress. And as such, teaching has been labeled a stressful occupation. This study was conducted to determine school teachers' level of occupational stress, commitment, job satisfaction and withdrawal cognition and their relationships. Due to the deficiency in models of teacher stress in the Malaysian context, this study also proposed and tested a model of teacher stress which includes attitudes, specifically organizational commitment and career commitment as moderating variables as well as organizational commitment, career commitment and job satisfaction as mediating variables Using questionnaires, data were obtained from 350 secondary school teachers in the state of Negeri Sembilan, West Malaysia, selected by random sampling. The data were used to test the hypothesized relationships. Reliability test, exploratory data analysis (EDA), frequency and percentages, Pearson's product moment correlation, hierarchical multiple regression analysis and structural equation modeling (path analysis) were employed to analyse the data.